Educational Strategies to Promote Student Diversity at the Elementary School Level - Forlin, Chris; Kafrawi, Shalahuddin (LJPI UI Bunga Bangsa Cirebon, 2024)
Purpose: This research explains the challenges of inclusion in the context of Mexican education policy and how they are addressed in elementary school classrooms. Methods: This research involves an ethnographic analysis of the practices of five teachers in elementary schools in Mexico City, focusing on teachers' perspectives on student diversity, the challenges they face in their daily activities, and the strategies they employ to overcome them. Results: The results of the analysis show that the inclusion approach does not only emerge due to the presence of students with special conditions or certain characteristics, but is also influenced by the teachers' attitudes towards students' difficulties and the efforts they make to advance learning. Despite the observed inclusion of practices, research also identifies the persistent influence of medical and psychological perspectives on student learning, behavior, and difficulties. This research highlights the need to broaden the focus on the work of teaching and create conditions that support inclusive education in the classroom. Conclusion: An inclusive approach to education is not only concerned with students with special needs or certain characteristics; This is also influenced by the teacher's attitude towards student difficulties and the efforts made to improve learning. Teachers' attitudes and actions during teaching also play an important role in promoting inclusivity, although inclusive practices already exist, research shows the ongoing impact of medical and psychological perspectives on students' education, behavior and challenges. Understanding these perspectives is important for overcoming student learning difficulties and promoting more effective and sustainable approaches to inclusion in education. The implications of this research confirm that an inclusive approach to education requires attention to students' needs as well as teachers' attitudes and actions in helping them overcome learning difficulties, with a deep understanding of the long-term impact of medical and psychological perspectives to increase the effectiveness of inclusion in the education system.